Endocrine and metabolic late effects in cancer survivors (Basel : Karger, 2021)
This book analyzes in detail all aspects related to endocrine and metabolic late effects observed in patients treated for cancer, both in childhood and adulthood. The chapters focusing on the possible pathogenic mechanisms of late effects (i.e., premature aging and chronic inflammation) and on bone health in cancer survivors are particularly interesting and innovative. The volume also deals with hypothalamic-pituitary, thyroid and gonadal disorders, including infertility and how to prevent it. Finally, the relationship between metabolic alterations and cardiovascular diseases in cancer survivors is addressed. Thanks to advances in cancer treatment and supportive care, the five-year survival rate of cancer patients is constantly increasing. However, this undisputable success of medicine has a flip side: the late adverse effects of anticancer therapies. Pediatric oncologists were the first to cope with late complications of treatments, but today also adult oncologists and onco-hematologists recognize the relevance of this issue. Even though late effects observed in cancer survivors can affect any organ or system, endocrine and metabolic dysfunctions are the most frequently reported. Endocrine complications rarely influence life expectancy of cancer survivors, but they can significantly impact morbidity and quality of life. Among endocrine adverse effects, severe hypothalamic damage may be considered the most harmful in survivors, leading to morbid obesity, propensity to metabolic syndrome and cardiovascular disease. This book aims to disseminate the knowledge about endocrine and metabolic adverse effects of cancer therapies and about survivorship care. Since the number of cancer survivors is steadily growing in the general population, this publication is intended not only for endocrinologists but also for oncologists, onco-hematologists, internists, pediatric specialists in those areas